Pengaruh Transparansi, Partisipasi Masyarakat dan Akuntabilitas Terhadap Pengelolaan Alokasi Dana Desa di Kecamatan Padamara - Pramesti, Kharunia; Amir, Amir; Wahyuni, Sri; Setyadi, Edi Joko (Lembaga Teewan Journal Solutions, 2026)
This study aims to empirically analyze the impact of transparency, community participation and accountability on the effectiveness of village fund management in Padamara Subdistrict. A survey method with a quantitative approach was used to collect information from the community and village officials who had participated in the village deliberation forum. Data analysis was conducted through multiple linear regression, which showed that the variables of transparency, community participation and accountability had a positive and significant influence on the management of village funds, with a contribution reaching 45.2%. The findings of the study identified that the level of information transparency, community participation and accountability strongly influence the successful management of village funds. Overall, this study concludes that increasing transparency, and community participation can improve accountability and the success of village fund management at the village level. This will also support the realization of good governance.